2017
DOI: 10.7150/thno.20251
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Tumor Effects of M1 Macrophage-Loaded Poly (ethylene glycol) and Gelatin-Based Hydrogels on Hepatocellular Carcinoma

Abstract: Background and Aims: Recently we reported that direct injection of M1 macrophages significantly caused tumor regression in vivo. Despite the promising result, a major limitation in translating this approach is the induction of acute inflammatory response. To improve the strategy, a biocompatible scaffold for cell presentation and support is essential to control cell fate. Here, we aimed to elucidate the anti-tumor effects of a poly(ethylene glycol) diacrylate (PEGdA) and thiolated gelatin poly(ethylene glycol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…A recent in vitro study reported that polypeptide-conjugated Ppy-coated metal electrode displays excellent cytocompatibility 43 , 44 . Gelatin, a natural polymer, can be self-crosslinked into a monomolecular or network structure in dilute solutions 45 - 47 . In this study, as shown in Scheme 1 , GelMA was used as a shape-inducer and a toxicity-neutralizer to form the GelMA-Ppy nanoparticles during the process of oxidative polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…A recent in vitro study reported that polypeptide-conjugated Ppy-coated metal electrode displays excellent cytocompatibility 43 , 44 . Gelatin, a natural polymer, can be self-crosslinked into a monomolecular or network structure in dilute solutions 45 - 47 . In this study, as shown in Scheme 1 , GelMA was used as a shape-inducer and a toxicity-neutralizer to form the GelMA-Ppy nanoparticles during the process of oxidative polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Engineered implantable scaffolds could be used to modulate local immune cells and improve cancer treatments. Guerra et al used hydrogels to deliver M1‐like macrophages directly to the tumor to utilize their antitumor activity and overcome acute inflammation associated with systemic injection of M1‐like macrophages . Poly(ethylene glycol) diacrylate (PEGdA) was crosslinked with thiolated gelatin poly(ethylene glycol) (Gel–PEG–Cys) and subsequently loaded with THP‐1 monocytes, polarized to M1‐like macrophages with LPS and IFN‐ γ.…”
Section: Localized Tam Modulation By Biomaterials: Lessons From Woundmentioning
confidence: 99%
“…2 Moreover, M1 macrophages produce cytokines, such as IL-1β, tumor necrosis factor (TNF)α), interferon (IFN)-γ, interleukin (IL)-12 and IL-23, thereby stimulating tumor immunity mediated by cytotoxic lymphocytes, nature killer (NK) cells and CD8 + T cells. [3][4][5][6] As CD11c and MHC II were reported to highly expressed in M1-like macrophages, these two molecules are widely used as the markers of M1 macrophages. [7][8][9] The tumor progresses, the tumor microenvironment changes from type 1-to type 2-immunity status.…”
Section: Introductionmentioning
confidence: 99%